Bmal1 Regulates Coagulation Factor Biosynthesis in Mouse Liver in Streptococcus oralis Infection - Chen, Lili; Li, Shue; Nie, Jiaming; Zhao, Jiajia; Yu, Shaoling; Li, Yaoxu; Peng, Jinfeng (Frontiers in Cellular and Infection Microbiology, 2020)
Streptococcus oralis (S. oralis) has been recognized as a fatal pathogen to cause multiorgan failure by contributing to the formation of microthrombus. Coagulation and fibrinolysis systems have been found under the control of circadian clock genes. This study aimed to explore the correlation between BMAL1 and coagulation factor biosynthesis in S. oralis infection. Mice were administered S. oralis to induce sepsis, and HepG2 cells were also infected by S. oralis. The expression of BMAL1 of hepatocytes was downregulated in the S. oralis infection group, leading to the downregulation of coagulation factor VII (FVII) and the upregulation of the coagulation factor XII (FXII) in vitro and in vivo. Furthermore, we confirmed that the deficiency of BAML1 contributed to the elevation of FVII and the decline in FXII by constructing BMAL1-deficiency (Bmal1−/−) mice. The current result showed that BMAL1 regulates FVII directly. Thus, a novel insight into the coagulation abnormality in S. oralis infection was gained that may optimize the treatment of sepsis by rescuing the expression of BMAL1 in the liver.